Prognostic values of EORTC QLQ-C30 and QLQ-HCC18 index-scores in patients with hepatocellular carcinoma – clinical application of health-related quality-of-life data. Issue 1 (December 2017) - Li, Leung; Mo, Frankie; Chan, Stephen; Hui, Edwin; Tang, Nelson; Koh, Jane; Leung, Linda; Poon, Annette; Hui, Joyce; Chu, Cheuk; Lee, Kit; Ma, Brigette; et al.
Abstract Background Health-related quality-of-life (HRQOL) assessment with EORTC QLQ-C30 was prognostic for overall survival (OS) in patients with advance-stage hepatocellular carcinoma (HCC), but no data existed for early-stage patients. The HCC-specific QLQ-HCC18 has not been evaluated for prognostic value in HCC patients. Utilization of raw HRQOL data in clinical setting has been impractical and non-meaningful. Therefore we developed index scores of QLQ-C30 and QLQ-HCC18 in an attempt to enable clinical utilization of these HRQOL measurements. This study investigates the prognostic significance of QLQ-C30, QLQ-HCC18 and C30/HCC18 index-scores in patients with newly diagnosed HCC which encompasses all stages. Methods From 2007–2011, 517 patients were prospectively recruited. HRQOL was assessed at diagnosis using QLQ-C30 and QLQ-HCC18; C30 and HCC18 index-scores were calculated from raw HRQOL data. Cox regression was performed using continuous, dichotomized QLQ-C30 and QLQ-HCC18 variables, or index-scores, together with clinical factors to identify independent factors for OS. Various multivariate models were validated with c-index and bootstrapping for 1000 replications. Results Four hundred and seventy two patients had complete HRQOL data. Their median OS was 8.6 months. In multivariate analysis, independent prognostic HRQOL variables for OS were QLQ-C30 pain (HR 1.346 [1.092–1.661], p = 0.0055), QLQ-C30 physical functioning (HR 0.652 [0.495–0.860], p = 0.0024); QLQ-HCC18 pain (HR 1.382 [1.089–1.754], p = 0.0077) and QLQ-HCC18 fatigue (HR 1.441 [1.132–1.833], p = 0.0030). C30 index-score (HR 2.143 [1.616–2.841], p < 0.0001) and HCC18 index-score (HR 1.957 [1.411–2.715], p < 0.0001) were highly significant factors for OS. The median OS of patients with C30 index-score of 0–20, 21–40, 41–60, 61–100 were 16.4, 7.3, 3.1, 1.8 months respectively (p < 0.0001); while for HCC18 index-score: 16.4, 6.0, 2.8, 1.8 months respectively (p < 0.0001). All the multivariate models were validated, with mean optimism <0.01. The bootstrap validated c-index was 0.78. Conclusions QLQ-C30 and QLQ-HCC18 were prognostic for OS in patients with newly diagnosed HCC irrespective of stage. Both C30 and HCC18 index-scores were highly significant prognostic factors for OS in newly diagnosed HCC patients. Index-scoring provides an effective way to summarize, analyze and interpret raw HRQOL data, and renders QLQ-C30 and QLQ-HCC18 meaningful and communicable in clinical practice. Index-scores could potentially serve as a standardized tool for future HRQOL research.